ANTROPOLOGI SASTRA DALAM CERITA RAKYAT GADIS BERMATA BIRU DAN TOLIRE MA GAM JAHA [Literature Anthropology in Gadis Bermata Biru and Tolire Ma Gam Jaha] - Riskal Ahmad (Kantor Bahasa Provinsi Maluku, 2020)
Folklore, legend, fairy tales are the result of people's thoughts in the past that were born to answer the phenomena surrounded the community. The results of this thought are then acknowledged with high believes so that it becomes a guideline for connecting with other human beings and for their relationship with nature. This study aimed to describe the literary anthropology in the Gadis Bermata Biru folklore and describe the literary anthropology in the Tolire ma Gam Jaha folklore. This research is a type of library research. The data werean anthology of folklore titled Pohon Cengkih Berbuah Emas and Ternate Oral Literature. The method used in this research wasthe descriptive qualitative method. Based on the results of the analysis, obtained (1) three of the four aspects have been found in the folklore